Integrated Dataset of Brazilian Flights - Teixeira, Claudio; Giusti, Lucas; Soares, Jorge; Santos, Joel dos; Amorim, Glauco; Ogasawara, Eduardo (Anais do Brazilian e-Science Workshop (BreSci); 2021: Anais do XV Brazilian e-Science WorkshopDO - 10.5753/bresci.2021.15793, 2021)
The Brazilian commercial aviation system achieved the first position among Latin American countries and the fifteenth place worldwide on the Revenue Passenger-Kilometer ranking. The availability of flight information, including meteorological conditions, enables studies about the Brazilian flight system, such as flight delays and timetabling. Therefore, this paper contributes to such studies by offering an integrated dataset containing data on departure and arrival for flights departing and arriving at Brazilian airports comprising the period from 2000 to 2019. This paper presents a dataset composed of 15, 505, 922 records of flight data, each containing 45 attributes. The attributes include data regarding the airline, flight, airports, meteorological conditions, scheduled and elapsed times for departure and arrival.